Implementation of Cooperative Learning Model by Greeting and Question Technique to Improve the Learning Outcomes and Activities Students in SMA 1 Bengkulu - Habibi Hidayat; Salastri Rohiat; Amrul Bahar (International Journal of Chemistry Education Research, 2019)
Cooperative learning model is one learning model of activities and interactions between students to motivate each other and help each other in mastering subject matter to achieve maximum achievement. This research was conducted in n cycles. Each cycle is carried out by the changes to be achieved starting from initial reflection to returning to analysis and reflection. The average value of students has increased in each cycle of 50.75 in cycle 1, then increased in cycle 2 that is equal to 52.2 and cycle 3 to 72.75. teacher activity during the chemistry learning process in the classroom for each cycle using the type cooperative learning model with greeting and questions techniques continued to increase namely from an average score of 30 to 34.5 and increased very well in the cycle to 3 which is equal to 42 with good criteria while for student activity the average score of 26 to 31.5 and increased very well in the third cycle that is equal to 39 with good criteria. The conclusion is that the implementation of cooperative learning model with greeting and question techniques can improve the learning outcomes and activities of students in SMA 1 Bengkulu.